2009
DOI: 10.3892/ijmm_00000322
|View full text |Cite
|
Sign up to set email alerts
|

The functional and compositional properties of lipoproteins are altered in patients with metabolic syndrome with increased cholesteryl ester transfer protein activity

Abstract: Abstract.To compare the molecular composition and functional differences at the lipoprotein level, we analyzed individual lipoprotein fractions from male patients with metabolic syndrome (MetS) (n=10) and gender-and age-matched healthy controls (n=14). The MetS group had significantly higher obesity, blood pressure, serum cholesterol, triglyceride (TG), adiponectin, and uric acid levels than the control group, while the serum blood urea nitrogen and creatinine levels of the MetS group were in the normal range.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…HDL3 PON-1 and non-HDL3 PON-1 activities have been evaluated in the different metabolic diseases related with obesity and discordant results have been reported in these studies. 29,30 No statistically significant differences have been observed between type 2 diabetes mellitus and control group in terms of HDL3…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…HDL3 PON-1 and non-HDL3 PON-1 activities have been evaluated in the different metabolic diseases related with obesity and discordant results have been reported in these studies. 29,30 No statistically significant differences have been observed between type 2 diabetes mellitus and control group in terms of HDL3…”
Section: Discussionmentioning
confidence: 94%
“…29 However, similar to our study, Park et al found lower HDL3 PON-1 activity in patients with metabolic syndrome than age matched healthy controls. 30 TA B L E 2 Comparisons of laboratory between groups in the lipoprotein. 11,12 Thus, we think that reduced activity of total PON-1 HDL3 PON-1 and non-HDL3 PON-1 are account for the increased oxidant, inflammatory and atherogenic status in obese.…”
Section: Discussionmentioning
confidence: 99%